The significance of GHRM in fostering hospitality employees' green creativity: A systematic literature review with bibliometric analysis. Issue 7 (3rd October 2022) - Choudhary, Parul; Datta, Amit
Abstract: The current business environment requires integration of business strategies that incorporate the characteristics and effectiveness of business goals along with environmental and societal interest. This study aims to explore the relationship between 'green human resource management' (GHRM) and 'employee green creativity' (EGC) in context to tourism and hospitality. Systematic review of the literature and bibliographic analysis are presented to analyse published work on the subject and to identify the research gap for future studies. This article initially shortlisted 52 publications from the Scopus database, but after a detailed screening, only 11 were identified which discusses both the GHRM and EGC in hospitality context. This is the first research to conduct a systematic review and bibliometric analysis of the variables GHRM and EGC in the hospitality domain, and it demonstrates that GHRM has impact on EGC.